Prevention of violence against elderly people - Juliana Ribeiro da Silva Vernasque; Carolina Silva Falarino; Vanessa Masfély Rocha; Samara de Lima Silva; Miriam Fernanda Sanches Alarcon; Maria José Sanches Marin (Cogitare Enfermagem)
Objective: To develop an educational bingo-type game related to the prevention of violence against elderly people and to analyze learning from its application.